Investigation of Pulse Electric Field Effect on HT29 Cell Alignment Properties Cultured on Laminin Micro-Patterned Surface - Buhari Mamman, Hassan; Mahadi Abdul Jamil, Muhammad; Ahmed Bawa, Mohammed; Nazib Adon, Mohamad (International Journal of Engineering and Technology, 2018)
Pulse electric field (PEF) is a way of generating transient holes in the cell membrane. This is achieved by exposing the cell to a high voltage electric field of usually of short duration. The application of PEF to the cell cannot only open pores in the cell membrane but can also affect the cell physiology. Extracellular matrix protein is the major regulator of many cellular functions such as proliferation, adhesion and migration. PEF was also found to modulate these cellular behaviours. However, a combined influence of PEF and ECM on cellular behaviour which could further enhances the cellular processes for wound healing application via directed cell migration has not been investigated. Therefore, the aim of this study is to examine the effect of PEF in combination with ECM on the cell guidance and self-assemble monolayer of HT29 cell line. Cell alignment was investigated via micro-contact printing techniques. The results of the study have shown that PEF has improved the HT29 cell alignment and elongation by more than 40%. Since tissue development in multicellular organisms in the course of wound healing depends on the cell adhesion process which can be influence by electrostatic charges. Therefore, manipulation of substrate charge by patterning the substrate and application of PEF to enhance cell adhesion is a promising scheme that can regulate cell guidance for wound healing application.Â Â Â